Assessing Trans-Inhibition of OATP1B1 and OATP1B3 by Calcineurin and/or PPIase Inhibitors and Global Identification of OATP1B1/3-Associated Proteins - John T. Powell; Ruhul Kayesh; Alexandra Ballesteros-Perez; Khondoker Alam; Pascaline Niyonshuti; Erik J. Soderblom; Kai Ding; Chao Xu; Wei Yue (MDPI AG, 2023)
Organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 are key determinants of drug-drug interactions (DDIs). Various drugs including the calcineurin inhibitor (CNI) cyclosporine A (CsA) exert preincubation-induced trans-inhibitory effects upon OATP1B1 and/or OATP1B3 (abbreviated as OATP1B1/3) by unknown mechanism(s). OATP1B1/3 are phosphoproteins; calcineurin, which dephosphorylates and regulates numerous phosphoproteins, has not previously been investigated in the context of preincubation-induced trans-inhibition of OATP1B1/3. Herein, we compare the trans-inhibitory effects exerted on OATP1B1 and OATP1B3 by CsA, the non-analogous CNI tacrolimus, and the non-CNI CsA analogue SCY-635 in transporter-overexpressing human embryonic kidney (HEK) 293 stable cell lines. Preincubation (10-60 min) with tacrolimus (1-10 µM) rapidly and significantly reduces OATP1B1- and OATP1B3-mediated transport up to 0.18 ± 0.03- and 0.20 ± 0.02-fold compared to the control, respectively. Both CsA and SCY-635 can trans-inhibit OATP1B1, with the inhibitory effects progressively increasing over a 60 min preincubation time. At each equivalent preincubation time, CsA has greater trans-inhibitory effects toward OATP1B1 than SCY-635. Preincubation with SCY-635 for 60 min yielded IC50 of 2.2 ± 1.4 µM against OATP1B1, which is ~18 fold greater than that of CsA (0.12 ± 0.04 µM). Furthermore, a proteomics-based screening for protein interactors was used to examine possible proteins and processes contributing to OATP1B1/3 regulation and preincubation-induced inhibition by CNIs and other drugs. A total of 861 and 357 proteins were identified as specifically associated with OATP1B1 and OATP1B3, respectively, including various protein kinases, ubiquitin-related enzymes, the tacrolimus (FK506)-binding proteins FKBP5 and FKBP8, and several known regulatory targets of calcineurin. The current study reports several novel findings that expand our understanding of impaired OATP1B1/3 function; these include preincubation-induced trans-inhibition of OATP1B1/3 by the CNI tacrolimus, greater preincubation-induced inhibition by CsA compared to its non-CNI analogue SCY-635, and association of OATP1B1/3 with various proteins relevant to established and candidate OATP1B1/3 regulatory processes.